Los delitos del estallido social y el rol de la Defensoría Penal Pública en Chile en 2019 - Farías, Javiera (2023)
The Constitution and the Code of Criminal Procedure, as well as international treaties ratified by Chile, oblige the state to offer free legal assistance to those who require it, which is especially relevant in the criminal sphere. On the riots or social unrest that occurred in Chile in the last quarter of 2019 and early 2020, the Public Criminal Defense Office adopted a set of measures to offer legal defense to those who were detained or indicted by the criminal prosecution bodies. This research compares crime behavior in the country between 2017 and 2021 and identifies the social unrest crimes. These are a group of crimes whose frequency increased considerably during the turbulent months: 1) burglary, 2) public disorder, 3) disturbances to public order, and 4) attacks and threats against authorities. The volume and specificities of the social unrest crimes challenged the entire justice sector and, in doing so, made it possible to generate beliefs about the legitimacy of the criminal justice system. In contexts of social unrest, the generation of such beliefs seems especially important, because they can increase perceptions of injustice, enhancing the motivations that give rise to such unrest. Therefore, the operational reactions deployed in the Public Criminal Defense Office to ensure timely criminal defense services are explained. Good practices of the Public Criminal Defense Office that could be strengthened institutionally and normatively so that the justice sector is better prepared to face complex or unusual criminological phenomena, such as those that occurred during the social outburst, are also highlighted.